Acute exacerbations of idiopathic pulmonary fibrosis (AE-IPF): an overview of current and future therapeutic strategies. (2nd April 2020) - Biondini, Davide; Balestro, Elisabetta; Sverzellati, Nicola; Cocconcelli, Elisabetta; Bernardinello, Nicol; Ryerson, Christopher J.; Spagnolo, Paolo
ABSTRACT: Introduction : Idiopathic pulmonary fibrosis (IPF), the most common of the idiopathic interstitial pneumonias, is a disease with a poor prognosis, and a highly heterogeneous and unpredictable clinical course. While most patients experience a relatively slow clinical, functional and radiological deterioration, a significant minority develops episodes of acute respiratory worsening termed acute exacerbations of IPF (AE-IPF). AE-IPF cannot be predicted or prevented and precede approximately half of IPF-related deaths. An international working group has recently proposed new diagnostic criteria and definition of AE-IPF. Areas covered : Despite their clinical significance, the optimal treatment of AE-IPF remains undetermined. In this review, we discuss the huge unmet need for an improved understanding of AE-IPF, with emphasis on current and potential therapeutic strategies. Expert opinion : The recently revised definition and diagnostic criteria of AE-IPF will facilitate future research into the etiology, pathobiology and clinical management of these life-threatening events. Efforts should be made to identify patients at higher risk for AE-IPF and detect early signs of these events. Potential treatment options should be studied in randomized, controlled trials. To this end, the importance of international collaborations cannot be overemphasized.